(untitled) - Belcaro, G; Nicolaides A N (London, 2000)
This book provides a brief overview of noninvasive vascular tests used to diagnose and quantify vascular problems. Also, it reports on tests concerning prevention and screening. The book is the result of the work of leading international experts in vascular investigations. It will be useful for all general practitioners, vascular technologists, and both physicians and surgeons, giving an introductory overview of the field.
Keywords: Venous Diseases; Bệnh tĩnh mạch; Vascular; Mạch máu